THREATS AND CHALLENGES OF MODERN GLOBALIZATION PROCESSES FOR NATIONAL STATES: TO THE PROBLEM OF POLITICAL RISK GOVERNANCE - Antypenko, I. (Pressing Problems of Public Administration, 2020)
The article deals with a topical issue of the public administration science, which has been poorly researched in Ukraine, as the ability of national states to cope with the political risks generated by modern globalization processes. The author specifies the impact of modern global threats such as terrorism, religious extremism, ethnic hostility, uncontrolled migration, cybercrime, illicit arms trafficking on national states.The influence of global political expansion and the problem of ensuring intergovernmental and inter-civilization compatibility are separately considered. It is noted that global political expansion is an objective process caused by conditions of globalization, which leads to a change in the system of value orientations inherent in a particular state, which results in the transformational influence of mentality, socio-cultural and political motivation, type of economic behavior, forms of interaction of ethnic groups and nations.An important problem that requires an immediate solution in the context of the political challenges of globalization is to ensure intergovernmental and inter-civilization compatibility. In this context, an important role is played by the relevant intergovernmental agreements, projects and programs that are based on the common opposition to international threats and offer strategic partnerships to overcome globalization challenges.The author concludes that modern globalization processes are in parallel with the processes of regionalization, localization and fragmentation of world politics, which further deepens political threats and challenges for national states. They have a good reason to refer terrorism, religious extremism, ethnic hostility, uncontrolled migration, cybercrime, illicit arms trafficking etc. to the modern political global threats. Strengthening the economic and military capacity of new players in the international arena, in particular China, the cardinal inter-ethnic difference between the cultures of the West and the East, is also a significant challenge for the present.Accordingly, the capacity of the state governance mechanism to overcome globalization challenges and threats and political risks generated by them should rely on strengthening sovereignty, realizing the national interest, modernizing the system of public administration, and developing a set of policy risk management tools.